Determining the circumstances of drowning injuries in communities North and South of the Philippine Archipelago. (1st March 2011) - Perez, M T A; Consunji, R; Navarra, A; Alag, L Joie
Abstract : Although analysis of existing data from the Department of Health and WHO on the Philippines show that 3000 Filipinos die annually, there are no details on where and how these drowning injuries occur. Safe Kids Philippines and the Philippine Life Saving Society embarked on conducting community surveys on drowning in the municipality of Los Banos, in Luzon Island and Iligan City in Mindanao Island to supplement national statistics with local information on circumstances surrounding drowning incidents and to identify determinants of and risk factors for conditions surrounding drowning injury. Drowning cases were identified through records in the local civil registries and the barangay (village) blotters. Interviewers traced resource persons who had first hand knowledge of the incidents. Verbal autopsies, using a standard validated questionnaire, uncovered 46 cases in Los Banos and 36 cases in Iligan City over the period 1996–2009. The most common site of drowning was open water – 77% of all cases happened in a lake, river or estuary. One in seven cases is associated with flash floods. Thirty-four per cent reported alcohol use prior to drowning, all of whom were adult males 23–65 years old. Contributory to drowning in children were the lack of adult supervision and the lack of the child's swimming skills among others. Focused group discussions in both cites recommended the inclusion of the local government units in creating and implementing regulations, incorporating water safety in the curriculum, creating first responder teams and conducting training on drowning prevention in the community.